Natural Frequencies and Modal Damping Ratios Identification of Civil Structures from Ambient Vibration Data - Minh-Nghi Ta; Joseph Lardiès; Berthillier Marc (Shock and Vibration)
Damping is a mechanism that dissipates vibration energy in dynamic systems and plays a key role in dynamic response prediction, vibration control as well as in structural health monitoring during service. In this paper a time domain and a time-scale domain approaches are used for damping estimation of engineering structures, using ambient response data only. The use of tests under ambient vibration is increasingly popular today because they allow to measure the structural response in service. In this paper we consider two engineering structures excited by ambient forces. The first structure is the 310 m tall TV tower recently constructed in the city of Nanjing in China. The second example concerns the Jinma cable-stayed bridge that connects Guangzhou and Zhaoqing in China. It is a single tower, double row cable-stayed bridge supported by 112 stay cables. Ambient vibration of each cable is carried out using accelerometers. From output data only, the modal parameter are extracted using a subspace method and the wavelet transform method.